Building bridges and strengthening positions: exploring the identity construction of immigrant bilingual teachers. Issue 6 (2nd July 2020) - Colliander, Helena
ABSTRACT: This study explores how bilingual teachers with an immigrant background construct professional identity in the context of initial literacy and second language teaching of adults. Specifically, the study seeks to understand what the teachers' membership of different work-related communities means for their professional identity and what capital the teachers use, negotiate and acquire to strengthen their positions in this professional field. The study is based on interviews with seven bilingual teachers. The data has been analysed from the perspective of situated learning theory and by employing some complementing concepts of Bourdieu used as thinking tools. The findings illustrate how the teachers construct their professional identity in relation to their students and by positioning themselves in different teacher communities. Moreover, the findings stress how the local school community plays a crucial part in determining the position the teachers obtain in the field. But in spite of being acknowledged as professionals, the teachers still need to negotiate their position by acquiring new capital and stressing the capital they already have.